The Monga Show: prototyping Amerindian Perspectivism through the girl-to-gorilla trick (Estudos em Design, 2019)
The Monga Show is the tropical version of the girl-to-gorilla trick, a sideshow act in which a beautiful lady mutates into an agitated gorilla, through an illusion technique called Pepper’s Ghost. This paper is a personal account of the process of building a mini Pepper’s Ghost illusion device, a prototype that emulates the Monga Show. Building this device led me to speculate on the possibility of it functioning as a model that prefigures Amerindian Perspectivism (Viveiros de Castro, 2004). The paper includes diagrams showing how the device works, and a brief discussion of the differences between the Pepper’s Ghost scene and the Monga Show act.